Be real, open, and creative: How openness to experience and to change mediate the authenticity-creativity association. (September 2021) - Xu, Xiaobo; Xia, Mengya; Zhao, Jingwen; Pang, Weiguo
Highlights: Authenticity, openness, and creativity are linked. Openness to experience mediates the authenticity-creativity association. This association is also mediated by openness to change. Openness is related to both subjective and objective creativity. Abstract: Although several researchers have suggested that authenticity fosters individuals' creativity, few empirical studies have focused on this research topic, and even fewer have examined the underlying mechanism. To address this gap, this study examined the relationships among authenticity, openness to experience, openness to change, and creativity. Three hundred Chinese participants (246 women, mean age = 20.36 years) were recruited via an online survey website and they were asked to complete the Authenticity Scale, the Openness to Experience Scale, the Routine Seeking Scale (i.e., as a measure of openness to change), the Creative Behavior Scale, and two divergent thinking tasks (i.e., the alternative uses task, AUT). The results revealed positive associations among all the variables of interest (i.e., authenticity, openness to experience, openness to change, self-reported creative behavior, AUT fluency, AUT originality, and AUT flexibility). Moreover, both openness to experience and to change fully mediated the association between authenticity and self-reported creative behavior, AUT fluency, and AUT flexibility. In addition, openness to experience fully mediated the link between authenticity and AUT originality. The results highlight the mediating role of openness as a mechanism that underlies the association between authenticity and creativity. Therefore, developing an authentic mindset or increasing individuals' propensity to openness could be considered possible ways to stimulate their creative potential/performance. The limitations of this study and future directions are discussed in detail.